Offsetting class privilege - Lawford-Smith, H (Oxford Uehiro Centre for Practical Ethics, 2016)
The UK is an unequal society. Societies like these raise significant ethical questions for those who live in them. One is how they should respond to such inequality, and in particular, to its effects on those who are worst-off. In this article, I’ll approach this question by focusing on the obligations of a particular group of those who are best-off. I’ll defend the idea of morally objectionable class-based advantage, which I’ll call ‘class privilege’, argue that class privilege can be non-culpable, and put forward an account of the obligations those with class privilege have. My main claim will be that those with class privilege have obligations to ‘offset’ their privilege, in something like the same way high emitters have obligations to offset their greenhouse gas emissions.